2006
DOI: 10.3319/tao.2006.17.4.739(gh)
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Structure in Marine Sediments with Gas Hydrate Reflectors in Offshore SW Taiwan, from OBS Data Tomography

Abstract: In the fall of 2004, four profiles of a total length of about 80 km and 24 recovered Ocean Bottom Seismometers (OBSs) were acquired along offshore southwestern Taiwan. These profiles were oriented in E-W and N-S directions to map the velocity structure of sediments by modeling the vertical component of OBS data. The thickness of sedimentary layers ranges from a few hundred meters to about 2 km, with the largest thickness being found beneath ridges. The most striking feature in the velocity models along E-W pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Compilation and analyses of geophysical and geological data have been carried out to establish the regional geophysical characters, geological structures, and sedimentary patterns of both the accretionary wedge province and the passive China continental slope regions of the investigation area. Special geophysical investigation techniques, such as 2.5-D (or pseudo 3-D) seismic surveys, ocean bottom seismometers (Cheng et al 2006;, heat flow measurements (Shyu et al 2006), deep-tow magnetic survey, etc., have been conducted. Regional sedimentary deposition processes (Yu and Huang 2006) and structural patterns have been proposed.…”
Section: Cgs Gas Hydrate Investigation Programmentioning
confidence: 99%
See 1 more Smart Citation
“…Compilation and analyses of geophysical and geological data have been carried out to establish the regional geophysical characters, geological structures, and sedimentary patterns of both the accretionary wedge province and the passive China continental slope regions of the investigation area. Special geophysical investigation techniques, such as 2.5-D (or pseudo 3-D) seismic surveys, ocean bottom seismometers (Cheng et al 2006;, heat flow measurements (Shyu et al 2006), deep-tow magnetic survey, etc., have been conducted. Regional sedimentary deposition processes (Yu and Huang 2006) and structural patterns have been proposed.…”
Section: Cgs Gas Hydrate Investigation Programmentioning
confidence: 99%
“…These datasets were collected using the high-resolution MCS system described above but with 400-to 250-m line spacing. OBSs were deployed along key profiles during each of the 3 2.5-D MCS surveys to provide velocity constrains (e.g., Cheng et al 2006), and to derive S-wave velocity information . Further analyses of these 2-D MCS/OBS experiments will be published later.…”
Section: Seismic Investigationmentioning
confidence: 99%
“…After erosion, the sub-seafloor temperature gradient redistributes and results in the hydrate/gas phase boundary moving downward. The results obtained in this study show that tectonic control is an important factor in determining bottomsimulating reflector (BSR) distributions offshore of southwestern Taiwan 121 .…”
Section: Research In Taiwanmentioning
confidence: 73%
“…Schnürle et al (2006) utilized three independent methods to determine the acoustic and shear-wave velocities of the sediments and investigate the gas hydrate content through rock physic modeling. Cheng et al (2006) found westward thrusting high velocity wedges along several east-west OBS profiles and suggested them as a series of thrust faults. Schnürle et al (2011) estimated fluid and gas migration path and intensity for the southern part of the Yuan-An ridge and found that the maximum fluid and gas transport across BSR should occur below the crest of anticlines.…”
Section: Resultsmentioning
confidence: 95%